1993
DOI: 10.1002/jez.1402650314
|View full text |Cite
|
Sign up to set email alerts
|

Cumulus oophorus as a sperm sequestering device, in vivo

Abstract: The cumulus oophorus, unique to the egg of eutherian mammals, has been suggested to function either in egg transport to the oviduct ampulla, in avoidance of polyspermy, in enhancement of sperm fertilizing ability, or in sperm guidance to the egg. To examine its role further, the content of the oviduct ampulla was collected at 0700-0730 h, 1130-1200 h, or 1600-1700 h on the day of ovulation from rats mated once or more than once, and analysed with an emphasis on sperm distribution in the ampullary fluid, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 40 publications
3
43
0
1
Order By: Relevance
“…HA oligosaccharides with 8 or more monosaccharide units were potent acceptors in the HC transfer reaction (Fig. 1B, lanes [5][6][7][8]. In these reactions, the size of the I␣I-reactive bands at the HC level increased with the size of the HA oligosaccharide, indicating that the HCs were actually transferred onto the oligosaccharides.…”
Section: Tnfip6-mediated Hcs Transfer From I␣i and P␣i To Hamentioning
confidence: 88%
See 1 more Smart Citation
“…HA oligosaccharides with 8 or more monosaccharide units were potent acceptors in the HC transfer reaction (Fig. 1B, lanes [5][6][7][8]. In these reactions, the size of the I␣I-reactive bands at the HC level increased with the size of the HA oligosaccharide, indicating that the HCs were actually transferred onto the oligosaccharides.…”
Section: Tnfip6-mediated Hcs Transfer From I␣i and P␣i To Hamentioning
confidence: 88%
“…This matrix is involved in the expulsion of the COC from the follicle (2), enhances the pickup and transport of the COC by the oviduct (3,4), and influences sperm penetration and oocyte fertilization (5)(6)(7). The cellular events of matrix formation, which include the synthesis and organization of hyaluronan (HA) around the cumulus cells, have been studied extensively in mouse COCs both in vivo and in vitro (8).…”
mentioning
confidence: 99%
“…Sperm are required to move through the extracellular matrix of the cumulus oophorus to achieve successful fertilization. It has been suggested that the cumulus oophorus attracts sperm via chemotaxis [54] and directs the few sperm that reach the ampulla to the immediate vicinity of the oocyte [55]. Thus, the cumulus oophorus has an important role in controlling the number of sperm that interact with the Zp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is suggested that chemoattractants originate both from mature oocytes and the surrounding cumulus cells [29[. Involvement of oocytes and their cumulus investments to divert spermatozoa towards the ova has been considered previously [30][31][32], but putative molecular mechanisms are still speculative [33]. In the pig, there is no experimental evidence of association of oocytes and sperm release.…”
Section: Discussionmentioning
confidence: 99%